Интонация как компонент семиозиса русских частиц - Tsoi, Aleksandr (Studia Rossica Posnaniensia, 2019)
The aim of this article is to focus on the role of intonation in the process of semiosis of Russian particles as language signs. Intonation is a non-lingual means of communication. It fulfills an auxiliary or independent function in the act of communication. In the process of communication Russian particles can intensify semantically important language information, or level it up. They can be expressers of explicit or latent/hidden intentions of its participants. From the point of view of semiotics intonation is an interpretation of a separate Russian particle as a language sign.